2021
DOI: 10.1186/s12890-021-01720-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arterial blood bicarbonate (HCO3−) concentration on the accuracy of STOP-Bang questionnaire screening for obstructive sleep apnea

Abstract: Background To evaluate the effect of arterial bicarbonate (HCO3−) concentration on the accuracy of STOP-Bang questionnaire (SBQ) screening for obstructive sleep apnea (OSA). Methods A total of 144 patients with suspected OSA were included. Polysomnograms (PSG) and blood gas analysis were performed, and the Epworth Sleepiness Scale (ESS), STOP-Bang questionnaire, and Berlin questionnaire were completed. The correlation between the arterial HCO3− con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The SBQ is widely used in different populations due to its simplicity and high sensitivity (Nagappa et al, 2015). Existing studies have improved SBQ diagnosis performance, e.g., by combining the SBQ with arterial blood HCO 3 concentrations (Pei & Gui, 2021), alternative scoring models (Chung et al, 2014), the weighted STOP‐Bang (Nahapetian et al, 2016), a simplified version of the SBQ‐B‐APNEIC score (Morinigo et al, 2022)and a two‐step approach (Chung et al, 2016). However, there are few studies that have considered gender differences when using the SBQ.…”
Section: Introductionmentioning
confidence: 99%
“…The SBQ is widely used in different populations due to its simplicity and high sensitivity (Nagappa et al, 2015). Existing studies have improved SBQ diagnosis performance, e.g., by combining the SBQ with arterial blood HCO 3 concentrations (Pei & Gui, 2021), alternative scoring models (Chung et al, 2014), the weighted STOP‐Bang (Nahapetian et al, 2016), a simplified version of the SBQ‐B‐APNEIC score (Morinigo et al, 2022)and a two‐step approach (Chung et al, 2016). However, there are few studies that have considered gender differences when using the SBQ.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported increased bicarbonate levels in OSA, in proportion to the apnea–hypopnea index ( Kaw et al, 2009 ; Chung et al, 2013 ; Eskandari et al, 2017 ; Pei and Gui, 2021 ), even in the absence of OHS ( Eskandari et al, 2017 ), in cohorts that were less likely to have OHS based on relatively low average BMIs ( Chung et al, 2013 ; Pei and Gui, 2021 ) and when comparing to BMI-matched controls ( Gold et al, 1993 ). OSA patients with frequent or long apneas may accumulate CO 2 during sleep ( Ayappa et al, 2002 ; Chung et al, 2013 ), leading to a compensatory increase of bicarbonate levels.…”
Section: Discussionmentioning
confidence: 99%
“…Obstructive sleep apnea-hypopnea syndrome (OSAHS) is a disorder characterized by apnea, decreased respiration, and decreased oxygen saturation level due to collapse of the upper airway, manifested by daytime sleepiness, fatigue, and inattention ( Pei and Gui, 2021 ). The signs and symptoms of OSAHS and FM are similar.…”
Section: Introductionmentioning
confidence: 99%
“…The signs and symptoms of OSAHS and FM are similar. Treatment of FM is ineffective, and patients with FM often experience sleep problems, fatigue, and pain ( Oka et al, 2020 ; Pei and Gui, 2021 ). Moldofsky et al originally defined FM syndrome as musculoskeletal pain, fatigue, and sleep disturbances ( Moldofsky et al, 1975 ).…”
Section: Introductionmentioning
confidence: 99%